2021
DOI: 10.53778/pjkd5477
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt’s Lymphoma in Kidney: A Rare Entity.

Abstract: Burkitt’s Lymphoma is an aggressive form of Non-Hodgkin’s Lymphoma, with higher incidence in children comprising 30% of pediatric lymphoma. The hallmark of which is a translocation involving c-MYC gene on chromosome 8. Burkitt’s Lymphoma comprises of 6.35% of all lymphoma cases in Pakistan, with male predominance. Lymphoma rarely presents as a primary pathology of acute kidney injury. Burkitt’s lymphoma in adult population is uncommon and few cases have been reported where Burkitt’s lymphoma presents as a caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similar observation was seen in an another study done in local population which showed that there is no change in eGFR ,serum creatinine and proteinuria was documented in their study of 36 patients. 9 Another study by Kara et al concluded that fasting is not associated with deterioration in renal status of CKD patients. 10 However, few studies have reported worsening of eGFR in patients with CKD stage-3 or above after fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observation was seen in an another study done in local population which showed that there is no change in eGFR ,serum creatinine and proteinuria was documented in their study of 36 patients. 9 Another study by Kara et al concluded that fasting is not associated with deterioration in renal status of CKD patients. 10 However, few studies have reported worsening of eGFR in patients with CKD stage-3 or above after fasting.…”
Section: Discussionmentioning
confidence: 99%